PENERAPAN MODEL MISSOURI MATHEMATICS PROJECT (MMP) DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS 5 SD PADA MATERI DATA - Yoshie, Kinar; Yurniwati; Engga Dallion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' mathematical communication skills through the application of the Missouri Mathematics Project (MMP) model in grade 5 of SDN Jati 03. This study uses a Classroom Action Research (CAR) approach which is implemented in three cycles with two meetings. Each cycle includes the planning, action, observation, and reflection stages. Data were obtained through written tests and observation sheets of teacher and student activities. The results showed a significant increase in students' mathematical communication skills from the pre-cycle by 17% to 52% in Cycle 1, increasing to 73% in Cycle 2, and reaching 93% in Cycle 3. This increase reflects the effectiveness of the Missouri Mathematics Project (MMP) model in developing students' mathematical communication skills such as the ability to express mathematical ideas, the ability to describe mathematical ideas, using mathematical terms and notations, the ability to describe visually, and the ability to interpret mathematical ideas. Therefore, this learning model is recommended as an innovative alternative to improve mathematical communication skills at the elementary school level, especially material regarding data.